Prevalence of vitamin D deficiency in chronic obstructive pulmonary disease and it’s correlation with forced expiratory volume in one second: a tertiary care centre study - S., Laxma Reddy; Avala, Ravicharan; Varma, Rajshekar; Narahari, Narendrakumar; K., Bhaskar; G. K., Paramjyothi (International Journal of Research in Medical Sciences, 2018)
Background: Vitamin D deficiency is common all over the Indian subcontinent, with a prevalence of 70-100% in the general population. Vitamin D deficiency has a role in several diseases of the respiratory system including chronic obstructive pulmonary disease (COPD). Studies have shown that vitamin D deficient COPD patients have lower lung function measured by FEV1. We conducted a study to see prevalence of Vitamin D deficiency in COPD patients and it’s correlation with Forced Expiratory Volume in 1 second. Methods: A cross sectional observational study was performed in a tertiary care hospital in Hyderabad, Telangana during the period of one and half year. This included 104 COPD cases attending outpatient department of pulmonary medicine. Serum vitamin D levels were measured, and spirometry was done in all patients and data was analyzed accordingly. Results: Among 104 patients, 87 were males and 17 were females. Most of the study population (44.2%) was aged between 60-70 years. Mean BMI was 26.40 (±5.77) kg/m2. Majority of study populations (66.34%) were in GOLD stage 1 and 2. The mean Vitamin D value of the study population was 20.77±11.74ng/ml. Majority of the COPD patients were vitamin D deficient (69.2%). 25.0 % was severely deficient of vitamin D. The mean FEV1 volume (%) was 83.15±11.53, 60.97±17.47, 30.71±7.96 in sufficient, deficient and severe deficient patients. Conclusions: Vitamin D deficiency is common in COPD patients. Serum vitamin D deficiency increases with increased severity of COPD. There is positive correlation between serum vitamin D levels and post bronchodilator FEV1 (%).